Contaminated water, stream sediments and soils close to the abandoned Pinhal do Souto uranium mine, central Portugal - Neiva, A. M. R. (2014)
The Pinhal do Souto mine exploited a quartz vein containing uranium minerals, mainly autunite and torbernite. This vein intersects a two-mica granite containing 10 ppm U and uraninite. The mine was exploited underground and produced 93,091 kg U3O8 between 1978 and 1989 and was then closed down. Two dumps were left in the mine area and these are partially covered by natural vegetation. Groundwater and surface water have a similar slightly acid-to-alkaline pH. The UO22 + is abundant and complexed with CO32 −, under neutral to alkaline pH. Metals and arsenic concentrations in the water increase during the dry season due to the evaporation. Uranium concentration in the water increases (up to 104.42 μg/l) in the wet season, because secondary uranium minerals are dissolved and uranium is released into the water. Soils tend to retain a higher concentration of several metals, including U (up to 336.79 mg/kg) than stream sediments (up to 35.68 mg/kg), because vermiculite from the former could adsorb it more easily than could kaolinite from the latter. The Fe-oxides precipitate retains the highest concentrations of several metals, including U and Th (up to 485.20 and 1053.12 mg/kg, respectively) and the metalloid As, because it is richer in oxyhydroxides and organic matter than stream sediments and soils. The median concentrations of Fe, As, Cd, Pb, Sb, Th, U, W and Zn in soils from this area are higher than in European soils of the FOREGS data. Waters from dry and wet seasons, stream sediments and soils are contaminated and must not be used. This area was compared with another Portuguese abandoned uranium mine area. The former mine caused a lower environmental impact attributable to it having lower sulphide concentration and mineral alteration than in the latter.